A Study Of Appraisers' Managerial Competencies Towards The Intentions Of Appraiser To Practice The Informal Performance Appraisal Process - Wong , Lee Wah (2009)
The first purpose of this study is to investigate the actual practice of the informal and unwritten performance appraisal process.Tujuan pertama kajian ini adalah lll1tuk memeriksa sarna ada kumpulan pengurus melakukan persediaan yang tidak formal tersebut sebelum penilaian prestasi pekerja.